1990
DOI: 10.1088/0031-9155/35/9/005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of backscatter factors for low energy radiotherapy (0.1-2.0 mm Al HVL) using thermoluminescence dosimetry

Abstract: Significant discrepancies of up to 10% exist between backscatter factors (BSF) recommended in a recent IAEA dosimetry Code of Practice (1987) compared with those published in Br. J. Radiol. Supplement 17 (1983), for the x-ray quality range 0.1-2.0 mm Al HVL. In an attempt to resolve this discrepancy, BSFs have been measured using thermoluminescence dosimetry (TLD) with small lithium borate chips, in order to minimise displacement effects associated with the use of larger volume ionisation chambers. Although su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…TLDs have been used for the dosimetry of kilovoltage x-ray beams with applications including measurements of skin doses (Ferguson et al 1995); dosimetric verification within tissue equivalent phantoms for comparing against planning system calculations (Alaei et al 2000); and quality assurance testing of kilovoltage x-ray beams (Nelson et al 2008). TLDs have also been used to measure BSFs of kilovoltage x-ray beams as mentioned elsewhere in this review (Coudin and Marinello 1998, Harrison et al 1990, Nelson and Hill 2011. It has also been shown that TLDs are suitable for the dosimetry of low energy brachytherapy sources with measurements in different solid phantoms (Meigooni et al 1988, Reniers et al 2004.…”
Section: Relative Dosimetry Of Kilovoltage X-ray Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLDs have been used for the dosimetry of kilovoltage x-ray beams with applications including measurements of skin doses (Ferguson et al 1995); dosimetric verification within tissue equivalent phantoms for comparing against planning system calculations (Alaei et al 2000); and quality assurance testing of kilovoltage x-ray beams (Nelson et al 2008). TLDs have also been used to measure BSFs of kilovoltage x-ray beams as mentioned elsewhere in this review (Coudin and Marinello 1998, Harrison et al 1990, Nelson and Hill 2011. It has also been shown that TLDs are suitable for the dosimetry of low energy brachytherapy sources with measurements in different solid phantoms (Meigooni et al 1988, Reniers et al 2004.…”
Section: Relative Dosimetry Of Kilovoltage X-ray Beamsmentioning
confidence: 99%
“…In two studies, lithium borate (TLD800) was used to measure BSFs for comparison with ionization chamber measurements and Monte Carlo calculations (Coudin andMarinello 1998, Harrison et al 1990). The study by Harrison et al (1990) was instrumental in identifying inaccuracies in published BSFs. The results from both studies found a good agreement between BSFs that were measured with TLDs and Monte Carlo calculations.…”
Section: Measured Bsfsmentioning
confidence: 99%
“…For ionization chambers there are competing effects: the displaced material in the chamber volume results in a lack of scatter being created within the chamber, and also more scatter occurring posterior to the chamber due to lack of attenuation (2) . There is also the concern with these chambers that extra scatter is being produced in the wall due to the physical size of the apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…Klevenhagen's work, along with the updated Monte Carlo simulations of Grosswendt and Knight, verified the new data, and an amalgamation of these three results was published in IPEMB as the new standard 9 , 10 . TLDs were used by Harrison to find BSF data that was not statistically different from the Monte Carlo data of Grosswendt 2 , 8 . Of note is the wide statistical deviation involved with using TLDs for exposure measurement as they can only be read once and are not extremely consistent.…”
Section: Introductionmentioning
confidence: 99%
“…The Monte Carlo method further allows simulation studies of scatter in terms of the scatter fraction, scatter-to-primary ratio and specific distribution of scattered radiation (Kalender 1981, Chan and Doi 1983, Johns and Yaffe 1983, Chan and Doi 1985, Bamea and Dick 1986, Papin and Rielly 1988. Backscatter factor calculations based on Monte Carlo method have been also reported (Chan and Doi 1981, Grosswendt 1984, Grosswendt 1990, Harrison et al 1990, IPSM 1991, Patrocinio et al 1996.…”
Section: Referencesmentioning
confidence: 99%